Comparison of bone marrow cell growth on 2D and 3D alginate hydrogels. - Barralet, J; Wang, L; Lawson, M; Triffitt, J; Cooper, P; Shelton, R (2005)
Calcium cross-linked sodium alginate hydrogels have several advantageous features making them potentially suitable as tissue engineering scaffolds and this material has been previously used in many biomedical applications. 3D cell culture systems are often very different from 2D petri dish type cultures. in this study the effect of alginate hydrogel architecture was investigated by comparing rat bone marrow cell proliferation and differentiation on calcium cross linked sodium alginate discs and 1mm internal diameter tubes. It was found that bone marrow cell proliferation was diminished as the concentration of alginate in the 2D hydrogel substrates increased, yet proliferation was extensive on tubular alginate constructs with high alginate contents. Alginate gel thickness was found to be an important parameter in determining cell behaviour and the different geometries did not generate significant alterations in BMC differentiation profiles.